Prevalence of hypertension is about 1–2% in African American girls and 0.5% in Caucasian girls aged 9 or 10 years, and prevalence increased with obesity. Issue 2 (12th January 2011) - Papandreou, Dimitrios
Abstract : Commentary on: Obarzanek E Wu CO Cutler JA . Prevalence and incidence of hypertension in adolescent girls . J Pediatr 2010 ;157 :461 –7, 467.e1–5 .